The expression of SALL4 is significantly associated with EGFR, but not KRAS or EML4-ALK mutations in lung cancer - Jia, Xiangbo; Qian, Rulin; Zhang, Binbin; Zhao, Song (Journal of Thoracic Disease, 2016)
Background: Lung cancer is the leading cause of cancer-related deaths worldwide; unfortunately, its prognosis is still very poor. Therefore, developing the target molecular is very important for lung cancer diagnosis and treatment, especially in the early stage. With this in view, spalt-like transcription factor 4 (SALL4) is considered a potential biomarker for diagnosis and prognosis in cancers, including lung cancer. Methods: In order to better investigate the association between the expression of SALL4 and driver genes mutation, 450 histopathologically diagnosed patients with lung cancer and 11 non-cancer patients were enrolled to test the expression of SALL4 and the status of driver genes mutation. This investigation included epidermal growth factor receptor (EGFR), kirsten rat sarcoma viral oncogene homolog (KRAS), and a fusion gene of the echinoderm microtubule-associated protein-like 4 (EML4) and the anaplastic lymphoma kinase (ALK). Results: The results of the study showed that females harbored more EGFR mutation in adenocarcinoma (ADC). The mutation rate of KRAS and EML4-ALK was about 5%, and the double mutations of EGFR/EML4-ALK were higher than EGFR/KRAS. In the expression analysis, the expression of SALL4 was much higher in cancer tissues than normally expected, especially in tissues that carried EGFR mutation (P